Sodium‐glucose co‐transporter‐2 inhibitors in patients with type 2 diabetes: Barriers and solutions for improving uptake in routine clinical practice. Issue 7 (30th March 2022) - Khunti, Kamlesh; Jabbour, Serge; Cos, Xavier; Mudaliar, Sunder; Mende, Christian; Bonaca, Marc; Fioretto, Paola
Abstract: Recent advances in type 2 diabetes (T2D) research have highlighted the benefits of sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors, including cardiovascular and renal protection. However, uptake rates of these drugs remain low in patients with T2D, particularly in subpopulations most likely to benefit from them. This review considers the potential barriers to prescribing SGLT‐2 inhibitors in T2D in clinical practice and outlines potential multidisciplinary recommendations to overcome these barriers. Safety concerns and a lack of clarity in and divergence of guidelines around the introduction of SGLT‐2 inhibitors into treatment regimens may represent a barrier to uptake from the clinicians' perspective, including a general lack of understanding of the benefits associated with SGLT‐2 inhibitors. Patient characteristics, such as socioeconomic status, may influence uptake because of the cost of SGLT‐2 inhibitors, especially in the United States, where health insurance coverage could be a concern. SGLT‐2 inhibitor prescription rates vary between clinical specialty (endocrinology, primary care, cardiology, and nephrology) and country, with cardiologists the lowest prescribers, and endocrinologists the highest. Primary care practitioners may experience more challenges in following SGLT‐2 inhibitor‐related guidelines than diabetes specialists as there may be fewer opportunities for education on how this drug class improves cardiovascular and renal outcomes in patients with T2D. Uptake rates appear to vary between countries because of differences in guidelines and health insurance systems. The amendment of SGLT‐2 inhibitor‐related guidelines for more multidisciplinary use and the implementation of patient and clinician education may encourage uptake of these drugs, potentially improving long‐term health outcomes among patients with T2D.